The Human Male Liver Is Predisposed to Inflammation Via Enhanced Myeloid Responses to Inflammatory Triggers - Kuipery, Adrian; Mahamed, Deeqa; Nkongolo, Shirin; D’Angelo, June Ann; Johnson Valiente, Alexandra; Mehrotra, Aman; Chapman, William C.; Horton, Peter; McGilvray, Ian; Janssen, Harry L. A.; Gehring, Adam J. (Frontiers in Immunology, 2022)
Background & Aim: Men have a higher prevalence of liver disease. Liver myeloid cells can regulate tissue inflammation, which drives progression of liver disease. We hypothesized that sex alters the responsiveness of liver myeloid cells, predisposing men to severe liver inflammation. Methods: Luminex was done on plasma from Hepatitis B Virus infected patients undergoing nucleoside analogue cessation in 45 male and female patients. We collected immune cells from uninfected livers of 53 male and female donors. Multiparametric flow cytometry was used to phenotype and characterize immune composition. Isolated monocytes were stimulated with TLR ligands to measure the inflammatory potential and the expression of regulators of TLR signaling. Results: We confirmed that men experienced more frequent and severe liver damage upon Hepatitis B Virus reactivation, which was associated with inflammatory markers of myeloid activation. No differences were observed in the frequency or phenotype of myeloid cells between male and female livers. However, monocytes from male livers produced more inflammatory cytokines and chemokines in response to TLR stimulation than female monocytes. We investigated negative regulators of TLR signaling and found that TOLLIP was elevated in female liver-derived monocytes Conclusions: Our data show that enhanced responsiveness of myeloid cells in the male liver predisposes men to inflammation, which was associated with altered expression of negative regulators of TLR signaling.